2013
DOI: 10.1002/art.37858
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Endogenous and Exogenous Glucocorticoid‐Induced Leucine Zipper in Animal Models of Inflammation and Arthritis

Abstract: Objective. Glucocorticoid-induced leucine zipper (GILZ) has effects on inflammatory pathways that suggest it to be a key inhibitory regulator of the immune system, and its expression is exquisitely sensitive to induction by glucocorticoids. We undertook this study to test our hypothesis that GILZ deficiency would exacerbate experimental immune-mediated inflammation and impair the effects of glucocorticoids on inflammation and, correspondingly, that exogenous GILZ would inhibit these events.Methods. GILZ ؊/؊ mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 43 publications
5
81
0
Order By: Relevance
“…However, GILZ KO mice did not present difference in severity of inflammation as compared with WT mice in a model of arthritis (13), although GILZ treatment using an adenoviral strategy was therapeutically effective. This latter study (13) is in agreement with our findings using LPS-induced inflammation, showing that absence of GILZ does not modify the severity or course of natural resolution of inflammation, but that an exogenous GILZ-based strategy efficiently resolves acute inflammation. Taken together, these studies indicate that GILZ may affect differently the outcome of inflammation resolution in different experimental models, possibly due to the fact that GILZ and AnxA1 influence each other's expression.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…However, GILZ KO mice did not present difference in severity of inflammation as compared with WT mice in a model of arthritis (13), although GILZ treatment using an adenoviral strategy was therapeutically effective. This latter study (13) is in agreement with our findings using LPS-induced inflammation, showing that absence of GILZ does not modify the severity or course of natural resolution of inflammation, but that an exogenous GILZ-based strategy efficiently resolves acute inflammation. Taken together, these studies indicate that GILZ may affect differently the outcome of inflammation resolution in different experimental models, possibly due to the fact that GILZ and AnxA1 influence each other's expression.…”
Section: Discussionmentioning
confidence: 82%
“…For instance, TAT-GILZ administration promoted a protective effect in a model of inflammatory bowel disease (9) and spinal cord injury (12). Moreover, recent studies showed that GILZ overexpression inhibits endothelial cell adhesion function (42) and protects against endotoxemia (43) and arthritis (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Males hemizygous for a knockout mutation in Tsc22d3 , from three independently generated strains (Bruscoli et al ., 2012; Ngo et al ., 2013a, 2013b; Romero et al ., 2012; Suarez et al ., 2012), are sterile due to the inability of spermatocytes to complete the first meiotic division. A few weeks after birth, hemizygous Tsc22d3 knockout males display Sertoli‐cell‐only seminiferous tubuli, which are totally devoid of germ cells.…”
Section: Resultsmentioning
confidence: 99%